Substantial Intestinal Microbiota Differences Between Patients With Ulcerative Colitis From Ghana and Denmark - Mirsepasi-Lauridsen, Hengameh Chloé; Vranckx, Katleen; Nielsen, Henrik Vedel; Andersen, Lee O’Brien; Archampong, Timothy; Krogfelt, Karen Angeliki; Petersen, Andreas Munk (Frontiers in Cellular and Infection Microbiology, 2022)
Backgrounds: Ulcerative colitis (UC) is a relapsing non-transmural inflammatory disease that is restricted to the colon and is characterized by flare-ups of bloody diarrhea. In this study, we aim to investigate intestinal bacterial diversity in healthy controls and patients with UC with and without active disease, from Ghana and Denmark. Methods: The study included 18 healthy controls, 9 UC patients with active and 9 UC patients with inactive disease from Ghana. Additionally, 19 healthy controls, 8 UC patients with active and 8 UC patients with inactive disease from Denmark were included in the study. Microbiota diversity analysis relied on the sequencing of ribosomal small subunit genes. Purified genomic DNA was submitted to PCR using a primer set targeting prokaryotes and eukaryotes. The purified DNA was sequenced on the Illumina MiSeq system in a 2 × 250 bp setup, Illumina. Analysis of the taxonomy table was performed blinded using BioNumerics-7.5, Applied Maths. Results: When analyzing the taxonomy data for prokaryotes, cluster and principal component analysis shows Danish healthy controls clustered together, but separate from healthy controls from Ghana, which also clustered together. The Shannon diversity index (SDI) for prokaryotes shows significant differences between Danish healthy controls and patients in comparison with the corresponding groups from Ghana, p= 0.0056. A significantly increased abundance of Escherichia coli was detected in healthy controls from Ghana in comparison to healthy controls from Denmark. The SDI of the eukaryotes ranges between 0 to 3.1 in the Ghana study groups, while in the Danish study groups it ranges between 2.4 to3.2, the difference is however not significant (p = 0.138). Our data show a significantly increased abundance of eukaryotes species in the healthy control group from Ghana and Denmark in comparison with patient groups from Ghana and Denmark. Conclusion: Overall, healthy controls and patients with UC from Denmark have increased the diversity of prokaryotic. Healthy controls from Denmark and Ghana have an increased abundance of eukaryotic in comparison to UC patient groups from Denmark and Ghana.